Coming Into Mindfulness: A Practice of Relational Presence to Cultivate Compassion in One Rural School (LEARNing Landscapes, 2021)
This narrative inquiry explores personal and professional stories of two educators, nurtured and supported by their school leadership, in a rural school setting, who have had diverse experiences with the contemplative practice of mindfulness. Our research primarily focused on the following wonders: How does the experience of mindfulness practice shift teacher identity and awareness, and the quality of time educators spend with children and youth? As educators, how can the practice of mindfulness expand our experience of listening, loving kindness, and compassion within educational spaces? We explore how their unique experiences of mindfulness are woven into the fabric of their school and a mindful pedagogy.
Keywords: mindfulness; compassionate; presence; teacher identity; mindful pedagogy